Physicians’ perception of the importance of ethical and deontological issues in a major Italian Province: pilot questionnaire and its validation - Ciliberti, Rosagemma; Baldelli, Ilaria; Gallo, Fabio; Patuzzo, Sara; De Stefano, Francesco; Bonsignore, Alessandro (Acta Biomedica Atenei Parmensis, 2019)
Background and aim: This study aims at validating a questionnaire on physicians’ knowledge and perception of deontological and ethical rules that guide the medical profession, in a major Italian Province. Methods: We designed an on-line survey questionnaire. Participants (N=200) were asked to fill in information regarding their demographic features and knowledge of the deontological code. Results: Concerning the preliminary data, the median total score on knowledge of the deontological code was 0.50. A significant difference in the total score was observed among education groups. Specifically, the median total score among subjects with a specialist qualification was significantly lower than among those with only a medical degree. Conclusions: The tested instrument and methodology appear to be efficacious and reliable. Our preliminary data indicate that knowledge of the rules concerning medical deontology and the related principles of medical ethics seems to be very limited. Therefore, the authors plan to implement a second phase of the study, which will consist of the questionnaire’ distribution to a broader and more representative sample.